Reformulation of Investment Partnerships to Overcome Inequality in UMKM Empowerment - Siska, Frency; Dewi Heniarti, Dini (Law Development Journal, 2026)
This study aims to analyze inequality in investment partnership practices in Indonesia within the framework of empowering micro, small, and medium enterprises (UMKM), as well as formulate a concept of equitable partnerships to overcome these inequality based on Aristotle's theory of justice and progressive law. The research method used is normative juridical with a legislative, conceptual, and case approach, supported by legal materials in the form of laws and regulations, court decisions, and scientific literature. The novelty of this research lies in the integration of the principles of distributive and corrective justice with progressive legal approaches as a comprehensive framework in reformulating investment partnerships oriented towards substantive justice for UMKM. The results of the study show that although normatively the regulation of investment partnerships has been directed at the empowerment of UMKM, in practice it actually causes structural inequality due to lack of transparency, weak supervision, and imbalance in bargaining positions. As a result, UMKM often bear disproportionate risks without getting fair benefits. This study proposes that investment partnerships be redesigned to ensure a proportionate distribution of benefits and risks and supported by effective corrective mechanisms. In addition, the progressive legal approach emphasizes the importance of the role of legal institutions in prioritizing substantive justice and protecting the weak. Thus, the reformulation of investment partnerships is important so that it functions as an instrument for empowering UMKM with equity, not just a formal contractual relationship.